Crisis Communication in the Post-Anesthesia Care Unit (PACU): Managing Risks and Improving Outcomes During Recovery in Three Saudi Arabian Tertiary Hospitals (2019–2024) - Abdulsalam Mohammed Aleid, Saud Nayef Salem Aldanyowi (Journal of International Crisis and Risk Communication Research, 2024)
Background: Effective crisis communication in the PACU is critical to patient safety, particularly in high-acuity, emergency contexts. However, limited evidence exists on how structured communication and culturally adapted approaches influence informed patient decision-making and outcomes in Saudi Arabia. Methods: This retrospective cohort study analyzed adults (≥18 years) who underwent emergency surgeries in three Saudi tertiary hospitals from January 2019 to September 2024. Data included patient demographics, nature of surgery, details of anesthesia-led risk discussions, use of decision aids, presence of structured handoff protocols, patient comprehension assessments, and postoperative complications. Multiple imputation was applied for missing data. Logistic regression identified predictors of improved informed consent quality and reduced medico-legal events. Results: Among several hundred patients, those who received structured, culturally sensitive communication interventions had significantly higher documented comprehension rates (p<0.05), fewer medico-legal complaints, and lower complication rates associated with communication failures. Logistic regression revealed that standardized handoff protocols, family involvement, and clear language explanations were independent predictors of improved outcomes (OR range: 1.5–2.3, p<0.05). Conclusion: Tailored crisis communication strategies in the PACU improve patient understanding, safety, and reduce medico-legal incidents in Saudi Arabian tertiary hospitals. Implementing structured protocols and culturally congruent explanations are key to enhancing informed decision-making and patient safety outcomes.